Climate disequilibrium dominates uncertainty in long‐term projections of primary productivity. (21st October 2022) - Felton, Andrew J.; Shriver, Robert K.; Stemkovski, Michael; Bradford, John B.; Suding, Katharine N.; Adler, Peter B.
Abstract: Rapid climate change may exceed ecosystems' capacities to respond through processes including phenotypic plasticity, compositional turnover and evolutionary adaption. However, consequences of the resulting climate disequilibria for ecosystem functioning are rarely considered in projections of climate change impacts. Combining statistical models fit to historical climate data and remotely‐sensed estimates of herbaceous net primary productivity with an ensemble of climate models, we demonstrate that assumptions concerning the magnitude of climate disequilibrium are a dominant source of uncertainty: models assuming maximum disequilibrium project widespread decreases in productivity in the western US by 2100, while models assuming minimal disequilibrium project productivity increases. Uncertainty related to climate disequilibrium is larger than uncertainties from variation among climate models or emissions pathways. A better understanding of processes that regulate climate disequilibria is essential for improving long‐term projections of ecological responses and informing management to maintain ecosystem functioning at historical baselines. Abstract : Rapid climate change may exceed ecosystems' capacities to respond through processes including phenotypic plasticity, compositional turnover and evolutionary adaption. However, consequences of the resulting climate disequilibria for ecosystem functioning are rarely considered in projections of climate change impacts. Here, we show that assumptions concerning the magnitude of climate disequilibrium are the dominant source of uncertainty, eclipsing uncertainties from variation among climate models or emissions pathways.